Fluoroscopic Sentinel Events in Neuroendovascular Procedures: How to Screen, Prevent, and Address Occurrence - Vance, A.Z.; Weinberg, B.D.; Arbique, G.M.; Guild, J.B.; Anderson, J.A.; Chason, D.P. (American Journal of Neuroradiology, 2012)
SUMMARY: Radiation-induced skin injury during fluoroscopic procedures has been recently addressed by The Joint Commission, which defined prolonged fluoroscopy resulting in a cumulative peak skin dose of ≥15 Gy to a single field as a sentinel event (FSE). Neuroendovascular procedures can be associated with a high radiation skin dose and present risks such as potential FSEs. Managing these risks is the responsibility of the interventional neuroradiologist. In this review, we discuss hospital policies needed for screening and preventing FSEs, methods for minimizing radiation-induced skin injury, and actions necessary to address potential FSEs once they have occurred. Abbreviations FSEfluoroscopic sentinel eventFTfluoroscopy timeKa,rreference air kermaPKAkerma-area productRCAroot cause analysisTJCThe Joint Commission